A Widespread Set of Late-Antique Annotations to Augustine’s "De Genesi ad litteram" - Keskiaho, Jesse 1979- (2016)
This article discusses a set of annotations found in the margins of most of the manuscripts of Augustine’s De Genesi ad litteram belonging to Michael Gorman’s β-family of texts of that work. These annotations survive as copies already in the earliest manuscript (the eighth-century Paris, Bibliothèque nationale de France, lat. 2607) and come in two distinct versions. After an analysis of their texts, palaeography (especially in the earliest manuscript), functions and themes of interest, this article argues that the annotations likely represent two stages in annotating Augustine’s text. Both versions appear to be considerably older than the first manuscript that transmits them and seem to have been created not much later than the sixth century, by an annotator or annotators employing notae antiquae. An edition of the annotations is presented in the Appendix.
Appendix auf Seite 110-127